Risk of meningioma associated with exposure of hormonal contraception. A case control study - Wahyuhadi, Joni; Heryani, Dini; Basuki, Hari (Majalah Obstetri & Ginekologi, 2018)
Objective: To determine the effect of hormonal contraceptive exposure on the development of meningioma. Materials and Methods: This case–control study, conducted in 2016, included all patients diagnosed histopathologically with meningioma between 2012 and 2013 and treated at Dr. Soetomo General Hospital, Surabaya, Indonesia. Medical record data from these patients were collected and compared with a control group consisting of non-meningioma patients who underwent contrast-enhanced head CT scans and direct interviews. A total of 101 cases and 101 controls were analyzed. Data were evaluated using univariate logistic regression analysis. Results: Patients with a history of hormonal contraceptive use had a 12.31-fold higher risk of developing meningioma (p = 0.000). In this study, women using monthly injectable contraceptives or oral contraceptive pills demonstrated a lower risk of meningioma compared to those using three-month injectable contraceptives. Participants who had used hormonal contraception for more than 10 years had an 18.216-fold increased risk of developing meningioma (p = 0.000). Histopathological analysis revealed no significant association between hormonal contraceptive history and meningioma subtype distribution; however, descriptive data indicated that the transitional type was the most frequent histopathological subtype among the case group. Conclusion: There is a significant association between hormonal contraceptive use and the occurrence of meningioma, particularly with the use of three-month injectable hormonal contraception and long-term use exceeding 10 years. No significant association was observed between meningioma histopathological grade and a history of hormonal contraceptive exposure.